1. Hu S, Sprintall J, Guan C, et al. Deep-reaching acceleration of global mean ocean circulation over the past two decades. Sci Adv. 2020;6(6):eaax7727. - Shijian Hu; Wenju Cai (TheScienceBreaker, 2020)
Adverse social determinants of health (SDOH) associate with greater heart failure (HF) risk. Among 9879 community-based participants of the Atherosclerosis Risk in Communities (ARIC) cohort study, we assessed 4955 plasma proteins using an aptamer-based platform (SomaLogic). We derived an SDOH factor comprising income, education, and area deprivation index (ADI) in Black and white participants. Proteins associated with this factor at Bonferroni significance were tested for associations with incident HF using multivariable Cox proportional hazard models. Among Black participants, 36 proteins were associated with both the SDOH factor and incident HF, 126 were among white participants, and 12 were shared between race strata. Eight of these demonstrated significant mediation effect in causal mediation models. Key results were replicated in 49,396 participants in UK Biobank. Mendelian randomization and colocalization suggested a potentially causal effect of C1q tumor necrosis factor-related protein 1 (C1QTNF1), an adiponectin paralog, on HF. We demonstrate protein biomarkers associated with SDOH burden and HF risk.